2020
DOI: 10.1371/journal.pone.0232725
|View full text |Cite
|
Sign up to set email alerts
|

Affective Temperaments and Meteoropathy Among Women: A Cross-sectional Study

Abstract: The main goal of the study was to assess the relationship between affective temperaments and meteoropathy among women and examine meteorosensitivity as a mediator in this relationship. The issue of affective temperaments and meteoropathy has not been considered in the literature. The sample consisted of 450 Caucasian women gathered via the online recruitment platform. The participants' ages ranged from 18 to 70 years (M = 30.01; SD = 9.10). The Polish version of the Temperament Evaluation of Memphis, Pisa, Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Among the older adults, however, the extracted personality profiles did not differ in meteorosensitivity or meteoropathy. Still, it should be noted that the older adults declared much higher meteorosensitivity and meteoropathy severity in comparison to the young adults, which was in line with our second hypothesis and other studies in this area [ 8 , 9 , 12 , 25 ]. The effect sizes of these differences were quite large (see Table 3 ), so we carefully assume that while personality profiles differed in both meteorosensitivity and meteoropathy levels in the young adult group, among older adults, meteorosensitivity and meteoropathy severity is high, and the seniors themselves vary so little with regard to these constructs that personality traits no longer matter.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the older adults, however, the extracted personality profiles did not differ in meteorosensitivity or meteoropathy. Still, it should be noted that the older adults declared much higher meteorosensitivity and meteoropathy severity in comparison to the young adults, which was in line with our second hypothesis and other studies in this area [ 8 , 9 , 12 , 25 ]. The effect sizes of these differences were quite large (see Table 3 ), so we carefully assume that while personality profiles differed in both meteorosensitivity and meteoropathy levels in the young adult group, among older adults, meteorosensitivity and meteoropathy severity is high, and the seniors themselves vary so little with regard to these constructs that personality traits no longer matter.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have observed that two demographic factors particularly contribute to individual differences in meteorosensitivity, which are age [middle- and especially old-aged individuals; e.g., 8 , 9 ] and gender, with an overrepresentation of women in this regard [ 10 , 11 ]. Not all meteorosensitive people develop the pathological reactions that compose meteoropathy; nevertheless, until very recently the mechanism responsible for meteoropathology at all was not entirely known [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is fairly well accepted that weather conditions can impact health, both physiologically and psychologically. The number of meteoropathic people (excessively sensitive to weather) is rising dramatically [1]. It is estimated that in the mid-twentieth century, every third person reacted to weather changes; currently, this group represents about half of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Strong weather stimuli may exacerbate symptoms in people with mental illnesses [1][2][3][4]. At such times, people sensitive to weather conditions may experience headaches and dizziness [5,6], changes in blood pressure [7], aggression [8], and accelerated heart rates [4].…”
Section: Introductionmentioning
confidence: 99%